Pengaruh Insentif Pajak dan Risiko Litigasi terhadap Konservatisme Akuntansi pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman di Bursa Efek Indonesia - Nainggolan, Marcellino Ropinus; Sirait, Devi Ayu Putri (Mahesa Research Center, 2025)
This study aims to examine the effect of tax incentives and litigation risk on accounting conservatism in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2022 period. Accounting conservatism is a principle of prudence in financial reporting that helps prevent information manipulation and provides protection against economic uncertainty. Tax incentives are considered a motivation for companies to adopt conservative reporting to minimize tax burdens, while litigation risk encourages caution to avoid potential legal claims. A quantitative approach was employed using multiple linear regression analysis. Data were collected from annual financial reports using purposive sampling, resulting in 81 observations. Before regression testing, classical assumption tests were conducted, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results show that both tax incentives and litigation risk have a significant effect on accounting conservatism, both partially and simultaneously. Tax incentives have a positive effect, while litigation risk harms accounting conservatism. The adjusted R² value of 0.348 indicates that 34.8% of the variation in accounting conservatism is explained by the two variables. These findings highlight the importance of considering fiscal and legal factors in preparing reliable and accountable financial statements.